Does Pricing Deviation of Exchange-Traded Funds Predict ETF Returns? - Lin, Jung-Chu (Asian Economic and Financial Review, 2017)
This paper investigates whether the pricing deviation of inactive exchange-traded funds (ETFs) differs from that of active ETFs and can predict future ETF returns better and longer. The results show that, compared to active ETFs, inactive ETFs trade at a substantial, more volatile, mostly negative and more skewed-to-the-right pricing deviation. Inactive ETFs’ pricing deviation relates significantly and negatively to longer-day future ETF returns, indicating that the deviation may predict ETF returns better and longer. However, if an inactive ETF has corresponding futures for its underlying index, its pricing deviation may shrink and pricing efficiency may increase.